2013
DOI: 10.1016/j.biomaterials.2013.06.040
|View full text |Cite
|
Sign up to set email alerts
|

Induction of angiogenesis using VEGF releasing genipin-crosslinked electrospun gelatin mats

Abstract: Rapid and controlled vascularization of engineered tissues remains one of the key limitations in tissue engineering applications. This study investigates the possible use of natural extracellular matrix-like scaffolds made of gelatin loaded with human vascular endothelial growth factor (VEGF), as a bioresorbable platform for long-term release and consequent angiogenic boosting. For this aim, gelatin was firstly electrospun and then cross-linked at two different concentrations (0.1% and 0.5% w/v) by using genip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
76
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 43 publications
3
76
0
1
Order By: Relevance
“…Thus, DSPP, DMP-1, and ON were selected as specific markers of differentiation to detect the odontogenic potential of hDPCs in the present investigation. Several recent studies showed that genipin-cross-linked scaffolds induced cell differentiation of various cell types (27,28,32). Similarly, our results indicate that genipin per se can be used for odontogenic differentiation of hDPCs.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Thus, DSPP, DMP-1, and ON were selected as specific markers of differentiation to detect the odontogenic potential of hDPCs in the present investigation. Several recent studies showed that genipin-cross-linked scaffolds induced cell differentiation of various cell types (27,28,32). Similarly, our results indicate that genipin per se can be used for odontogenic differentiation of hDPCs.…”
Section: Discussionsupporting
confidence: 69%
“…Recently, genipin and genipin-containing scaffolds have been investigated for their effects on the differentiation of cells (27,28). However, there was no previous information regarding the odontogenic effect of genipin in pulp cells for dentin-pulp complex engineering.…”
Section: Discussionmentioning
confidence: 98%
“…To overcome this obstacle, chemical immobilization of gelatin is an effective method [35], especially glutaraldehyde which is usually used to crosslink or immobilize gelatin onto the surface of microfibers or films [36][37][38]. The immobilization amount of gelatin on the surface of fibrous scaffold usually depends on the reactive groups.…”
Section: Introductionmentioning
confidence: 99%
“…3 Fibrous scaffolds fabricated by electrospinning have been used recently for biomedical applications because they can easily create a three-dimensional porous structure resembling the morphology of natural ECM. [4][5][6] The microstructure of electrospun scaffolds such as fiber diameter and porosity can be controlled by adjusting solution properties and operating parameters. Due to the large surface area to volume ratio of electrospun scaffolds, cell adhesion, migration, and proliferation improve.…”
mentioning
confidence: 99%